Quantitative analysis of scientific literature in forensic science. Issue 1 (2nd January 2017) - Ravichandra Rao, I. K.; Raghavan, K. S.; Bhargav, K. N.
Abstract : A search of WoS for research literature in Forensic Science was carried out for the purpose of identifying the contours of forensic science; the study revealed figures that were at considerable variance with the figures given in the paper by Kumar and Biradar. The study indicates that while both India and China have a significant presence in the global literature on forensic science, measured in terms of widely used indicators, the quality of research (in terms of citations received) is much below that of the global average. Much of Indian research emanated from government funded institutions. The study also aimed at identifying relation between the impact factor of the journal and the number of citations received by papers published in that.